Solid Oxide Fuel Cells based on Lanthanum Tungstates Electrolytes - Porras-Vázquez, José Manuel; Zayas-Rey, María José; Ramírez-Losilla, Enrique; Marrero-López, David; Dos-Santos-Gómez, Lucía (My University, 2015)
Lanthanum tungstate with composition La27W4NbO55- (LWNO) has been tested as proton conductor electrolyte for Solid Oxide Fuel Cells (SOFCs). For this purpose, different electrodes and composite electrodes are considered, including: La0.8Sr0.2MnO3-, La0.6Sr0.4Co1-xFexO3-, La0.5Sr0.5Cr0.5Mn0.5O3-, SrFe0.75Nb0.25O3- and NiO. Chemical compatibility between the cell components is investigated by X-ray powder diffraction (XRPD) and energy dispersive spectroscopy (EDS). Furthermore, area specific resistance (ASR) of the different electrodes is determined in symmetrical cells by impedance spectroscopy. XRPD and EDS analysis do not reveal significant bulk reactivity between most of these electrodes and LWNO electrolyte in the typical operating temperature range of a SOFC (600-900 ºC). However, minor interdiffusion of elements at the electrolyte/electrode interface affects both the ohmic losses and electrode polarization of the cells. ASR values are significantly improved by using a buffer layer of Ce0.8Gd0.2O1.9, between the electrolyte and electrode materials, to prevent reactivity. A single cell with 350 µm thick electrolyte, NiO-Ce0.8Gd0.2O1.9 anode and La0.6Sr0.4Co0.8Fe0.2O3- cathode, generates maximum power densities of 140 and 18 mWcm-2 at 900 and 650 ºC, respectively.
Keywords: Pilas de combustible; Proton conductor; Fuel cell test; Lanthanum tungstate